Thin plate splines for transfinite interpolation at concentric circles - Bejancu, Aurelian (Mathematical Modelling and Analysis, 2013)
We propose a new method for constructing a polyspline on annuli, i.e. a C 2 surface on ℝ2 0, which is piecewise biharmonic on annuli centered at 0 and interpolates smooth data at all interface circles. A unique surface is obtained by imposing Beppo Levi conditions on the innermost and outermost annuli, and one additional restriction at 0: either prescribing an extra data value, or asking that the surface is non-singular. We show that the resulting Beppo Levi polysplines on annuli are in fact thin plate splines, i.e. they minimize Duchon’s bending energy.